Effect of Lipoxin A4 on Lipopolysaccharide-Induced Endothelial Hyperpermeability - Huayan Pang; Pan Yi; Ping Wu; Zhuoya Liu; Zhongjie Liu; Jianming Gong; Hua Hao; Lei Cai; Duyun Ye; Yinping Huang (The Scientific World Journal)
Excessive oxidative stress, decreased antioxidant capacity, and enhanced cellular calcium levels are initial factors that cause endothelial cell (EC) hyperpermeability, which represents a crucial event in the pathogenesis of pre-eclampsia. Lipoxin A4 (LXA4) strongly attenuated lipopolysaccharide (LPS)-induced hyperpermeability through maintaining the normal expression of VE-cadherin and β-catenin. This effect was mainly mediated by a specific LXA4 receptor. LXA4 could also obviously inhibit LPS-induced elevation of the cellular calcium level and up-regulation of the transient receptor potential protein family C 1, an important calcium channel in ECs. At the same time, LXA4 strongly blocked LPS-triggered reactive oxidative species production, while it promoted the expression of the NF-E2 related factor 2 (Nrf2) protein. Our findings demonstrate that LXA4 could prevent the EC hyperpermeability induced by LPS in human umbilical vein endothelial cells (HUVECs), under which the possible mechanism is through Nrf2 as well as Ca2+-sensitive pathways.